1985
DOI: 10.1002/star.19850370103
|View full text |Cite
|
Sign up to set email alerts
|

The Starches of Dioscorea ballophylla and Amorphophallus campanulatus. Comparison with Tapioca Starch

Abstract: Starches frOln the tubers o f Dioscorra hallophylla and A morphophtrl-/us cumpanirlafrt.s were isolated and purified. Scanning electron niicroscopy of these starches exhibits cliptical, spherical or irregular shapes, respectively, while the shape of tapioca is spherical. Waterbinding capacity o f A . cumpanulatiis starch is very high in coniparison to D. ballophylla and tapioca starches but the amylose content is significantly less. Gelatinization temperature of both these starches is the same but it is higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 2 publications
5
23
2
Order By: Relevance
“…The good WAC of taro flour may prove useful in products where good viscosity is required, such as in soups and gravies. Soni et al observed that high water binding is attributed to loose association of starch polymers in the native granules [26]. The high WAC of taro flour could be attributed to the presence of higher amounts of carbohydrates in the flour.…”
Section: Water Absorption Capacitymentioning
confidence: 98%
“…The good WAC of taro flour may prove useful in products where good viscosity is required, such as in soups and gravies. Soni et al observed that high water binding is attributed to loose association of starch polymers in the native granules [26]. The high WAC of taro flour could be attributed to the presence of higher amounts of carbohydrates in the flour.…”
Section: Water Absorption Capacitymentioning
confidence: 98%
“…Yields of starch from diverse aroids ranged from 7 to 18.6% (wet basis), depending on the species, variety, and isolation method (Falade & Okafor, 2013;Moorthy, Unnikrishnan, & Lakshmi, 1994;P erez et al, 2005;Soni et al, 1985). Yields of starch from Amorphophallus paeoniifolius (10 genotypes) were 7e14.3% (Moorthy et al, 1994).…”
Section: Isolationmentioning
confidence: 98%
“…Yields of starch from X. sagittifolium (1 genotype) and C. esculenta (1 genotype) were 10e12% (wet basis) (P erez et al, 2005). Starch yields from some studies are hard to compare due to the different ways in which the results were expressed (dry weight basis vs wet weight basis) (Moorthy et al, 1994;Soni et al, 1985).…”
Section: Isolationmentioning
confidence: 99%
“…The peeled sliced and dried samples had the highest swelling index and water absorption capacity of 9.05 and 95.44%, respectively, while the abacha from boiled, peeled and sliced cassava had the least values of 7.24 and 68.50%, respectively. The high water binding capacity of the PSD samples may be attributed to a high proportion of undegraded starch granules (Soni et al, 1985;IITA, 2003) or to a lack of association of the starch polymers in the native granules. Increase in water absorption capacity in food systems enables bakers to manipulate the functional properties of dough in baked products (Omodamiro et al, 2007).…”
Section: Functional Propertiesmentioning
confidence: 99%